Dataverse.no - Longva, Leif; Conzett, Philipp; Aspaas, Per Pippin (Open Science Talk, 2022)
The service for open research datasets Dataverse.no was established in 2017. Five years later, it holds some 1,300 datasets created by researchers at fourteen partner institutions. All submitted datasets are curated (checked) before they are published by curators at the various institutions. In addition, curators have established courses and webinars helping researchers make their datasets as FAIR as possible (FAIR = Findable, Accessible, Interoperable, Reusable). In this episode, Leif Longva and Philipp Conzett tell about how it has expanded, from a subject-specific archive called TROLLing (Tromsø Repository of Language and Linguistics) to the generic, CoreTrustSeal-certified service that we see today.